Pengaruh Literasi Keuangan Syariah dan Religiusitas Terhadap Perilaku Konsumtif Pada Alumni Angkatan Ke-19 Pesantren Modern Daarul Uluum Lido - Muhamad Aksan Hanafi; Sofyan Muhlisin; Nurman Hakiem (CV. ITTC INDONESIA, 2025)
Today's consumer behavior has shifted, from initially merely fulfilling primary needs to now encompassing secondary, tertiary, and even complementary needs, with a tendency toward consumerism. Consumer behavior is the act of purchasing goods without consideration, prioritizing desires over needs. Fulfilling these changing needs is crucial for leading individuals toward a life in harmony with their environment. Excessive and uncontrolled consumer behavior can negatively impact individuals and society. This behavior should be avoided because it can lead to financial problems, stress, and waste of natural resources. The purpose of this study is to determine the significant influence of Islamic financial literacy and religiosity on consumer behavior. This study aims to determine the simultaneous influence of Islamic financial literacy and religiosity on consumer behavior. The approach used in this study is quantitative data. Quantitative data is data in the form of numbers or qualitative data that is quantified. The quantitative data in this study are the answers to the questionnaire distribution instrument, which are then quantified and presented in statistical form. The results of this study are that Islamic financial literacy partially does not influence consumer behavior, then religiosity partially does not influence consumer behavior, and Islamic financial literacy and religiosity simultaneously do not influence consumer behavior.